Study of Antibiotic Susceptibility among Bacterial Isolates in Neonatal Intensive Care Unit of a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Brajesh Raj Chaudhary; Kalpana Karmacharya Malla; Sajan Poudel; Brajesh Kumar Jha (Journal of Nepal Medical Association, 2020)
Introduction: Neonatal sepsis is a major cause of neonatal morbidity and mortality worldwide, especially in developing countries like Nepal. Antibiotic resistance among microorganisms poses new challenges in the treatment of neonatal sepsis. The present study is conducted with the objectives of determining clinico-bacteriological profile and antibiotic susceptibility among isolated bacteria in a neonatal intensive care unit.